Mapping lightning processes using fuzzy inference system - de Souza, A. N.; da Silva, I. N.; Zago, M. G.; Flauzino, R. A. (Institute of Electrical and Electronics Engineers (IEEE), 2002)
This paper describes a novel approach for mapping lightning processes using fuzzy logic. The core regarding lightning process is to identify and to model those uncertain information on mathematical principles. In fact, the lightning process involves several nonlinear features that our current mathematical tools would not be able to model. The estimation process has been carried out using a fuzzy system based on Sugeno's architecture. Simulation results confirm that proposed approach can be efficiently used in these types of problem.